Peran Media Sosial Sebagai Instrumen Kontrol Publik Terhadap Kinerja Birokrasi - Nur Aini; Nur Sakinah Mauliddia; Nurul Hidayahti Salsabilla; Amanda Nailathul Fadilah; Yulia Hanoselina; Yuliarti . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The development of digital technology has pushed social media into becoming a crucial instrument for public oversight of bureaucratic performance. This study aims to analyze the role of social media as a means of public control in enhancing transparency, accountability, and responsiveness of bureaucracy in the digital era. This study is based on role theory, which understands role as a dynamic element of a person's position in exercising their rights and duties. Social media acts as a bridge between two different systems, namely society and bureaucracy, so that society can behave according to the expectations of their environment as supervisors of public services. The method used is a descriptive qualitative approach using literature study and document analysis techniques. Data were obtained from various sources, such as scientific journals, books, research reports, laws and regulations, online news, and publications relevant to the research topic. Data analysis was conducted using content analysis techniques with the stages of data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that social media has transformed into a digital participation space that allows the public to convey criticism and complaints, as well as directly supervise public services. Social media also contributes to increasing bureaucratic transparency and accountability through the rapid and open dissemination of information. However, the effectiveness of digital public control is influenced by the public's digital literacy capacity, bureaucratic responsiveness to criticism, and digital media governance regulations. Furthermore, the emergence of viral-based policy has encouraged bureaucracies to respond quickly to public issues, despite the risk of producing reactive policies. Therefore, the integration of social media into formal bureaucratic oversight systems is necessary to support the realization of more transparent, accountable, responsive, and participatory governance.